Clinical Significance of Breast Cancer Molecular Subtypes and Ki67 Expression as a Predictive Value for Pathological Complete Response following Neoadjuvant Chemotherapy: Experience from a Tertiary Care Center in Lebanon - Ali Atoui; Maroun Bou Zerdan; Ahmad El Mahmoud; Nathalie Chamseddine; Lina Hamad; Hazem I. Assi (International Journal of Breast Cancer)
Introduction. Breast cancer is considered nowadays the most prevalent cancer worldwide. The molecular era has successfully divided breast cancer into subtypes based on the various hormonal receptors. These molecular subtypes play a major role in determining the neoadjuvant chemotherapy to be administered. It was noted that the use of neoadjuvant chemotherapy was associated with higher achievement of pathological complete response. The aim of the study was to determine the predictive role of breast cancer subtypes in the efficacy and prognosis of neoadjuvant chemotherapy regimens. Methods. Combining dose dense anthracycline-based, regular dose anthracycline-based, and nonanthracycline-based chemotherapy, we observed data from 87 patients with breast cancer who received surgery after administration of neoadjuvant chemotherapy at our institution between January 2015 and July 2018. The patients were classified into luminal A, luminal B, HER2 overexpression, and triple negative breast cancer as well as low Ki67 (≤14%) and high Ki67 (>14%) expression groups using immunohistochemistry. Pathologic complete response was the only neoadjuvant chemotherapy outcome parameter. To evaluate variables associated with pathologic complete response, we used univariate analyses followed by multivariate logistic regression. Results. 87 patients with breast cancer were classified into different subtypes according to the 12th St. Gallen International Breast Cancer Conference. The response rate to neoadjuvant chemotherapy was significantly different (p=0.046) between the subgroups. There were significant correlations between pathological complete response (pCR) and ER status (p<0.0001), HER2 (p=0.013), molecular subtypes (p=0.018), T stage (p=0.024), N stage before chemotherapy (p=0.04), and type of chemotherapy (p=0.029). Luminal B type patients had the lowest pCR, followed by luminal A type patients. Conclusion. Evaluating molecular subtype’s significance in breast cancer prognosis warrants additional studies in our region with extensive data about patient-specific neoadjuvant chemotherapy regimens. Our study was able to reproduce results complementary to those present in the literature in other outcomes.